(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Socio-political changes in the country, opening up the possibility of direct appeal to forbidden topics or to supposedly non-existent phenomena of socialist reality, expand the research field of psychology and make it possible to abandon the Aesopian language in science. The rehabilitation of names entailed the rehabilitation of scientific concepts and terms that qualified as bourgeois. One such concept is alienation. It became obvious that the phenomenon of alienation is by no means the prerogative of the "Western way of life" on the grounds that K. Marx, especially in his later works, used this concept to characterize alienated labor in antagonistic class societies.